1986
DOI: 10.1266/jjg.61.447
|View full text |Cite
|
Sign up to set email alerts
|

Sex ratio distortion in populations and its possible role in insect suppression : Experimental studies with strains of Drosophila melanogaster carrying cytoplasmically-inherited male-killing spiroplasmas.

Abstract: The possible role of cytoplasmic sex ratio (SR) distortion in insect population control has been assessed experimentally.In Drosophila melanogaster the agent responsible for SR distortion is a male-killing spiroplasma and SR strains are characterized by females producing daughters but few, if any, sons. Populations were constructed of wildtype and SR females (of various malekill effectivenesses) plus males, in different proportions.The frequency of females in the populations was monitored regularly.Under some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…It would be nonsense to pretend that the above model for early male killing is in any way an accurate predictor of the equilibrium frequency of cytoplasmic male killers (which is typically at around 10% (Ikeda 1970;Fitz-Earle & Sakaguchi 1986)). There is no allowance made for either any potential affect on fitness associated with the infection in females or the effect of the distortion of sex ratio.…”
Section: Late Male Killingmentioning
confidence: 99%
“…It would be nonsense to pretend that the above model for early male killing is in any way an accurate predictor of the equilibrium frequency of cytoplasmic male killers (which is typically at around 10% (Ikeda 1970;Fitz-Earle & Sakaguchi 1986)). There is no allowance made for either any potential affect on fitness associated with the infection in females or the effect of the distortion of sex ratio.…”
Section: Late Male Killingmentioning
confidence: 99%
“…So far no male‐killing endosymbiont has been found in any natural population of D. melanogaster (Fitz‐Earle & Sakaguchi, 1986; Hurst, 1993). We report here for the first time the occurrence of a sex‐ratio trait in this species which is maternally inherited, infectious and caused by early MK.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have demonstrated that sublethal exposure to a variety of chemicals and pesticides can induce persistent disruptions in learning and memory (Aliouane et al 2009, Frost et al 2013, Siviter et al 2018). Similar patterns of reduced learning and memory in honeybees can be attributed to parasitic infection and environmental conditions, including temperature extremes and changes in light exposure (Fitz-Earle and Sakaguchi 1986, Frost et al 2011, Gegear et al 2006, Kralj et al 2007, Charbonneau et al 2016). Pest management strategies must, therefore, take into consideration potential negative consequences of pesticides, physical barriers, and other treatment options on pollinators and other beneficial insects.…”
Section: Challenges Associated With Insect Learning and Pest Managementmentioning
confidence: 83%
“…Use of sterile males is a useful strategy to mediate a variety of insects; however, results can vary among species or populations and are limited among insect species that mate with multiple partners (Fitz-Earle and Sakaguchi 1986). Many parasites and bacterial or viral pathogens are known to affect changes in host behavior, survival, resistance, and fecundity (Hurst and Jiggins 2000, Goodacre and Martin 2012).…”
Section: Future Directions For Pest Managementmentioning
confidence: 99%